Kindheit in Byzanz : Emotionale, geistige und materielle Entwicklung im familiären Umfeld vom 6. bis zum 11. Jahrhundert - Ariantzi, Despoina (2012)
Although there have been many studies of childhood in Ancient Greece and Rome and in the Middle Ages in the West, there is no such study for the Byzantine world. To fill the gap, this bookreconstructs the most important factors in childhood in Byzantium from the 6th through the 11th century. The main sources are the lives of the saints, which are of central importance for the analysis of the social history and daily life of the population. They also provide an insight into family, social and economic structures, as well as patterns of behaviour. This material is supplemented by legal, medical, theological and other sources.